DOES TEAMWORK, CAREER DEVELOPMENT, SELF DEVELOPMENT INFLUENCE WORK INVOLVEMENT? - Ramaditya, Muhammad (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2020)
This study aims to investigate the influence of teamwork and career development on self development and work involvement of employees.  This study conducted in the Jakarta BPJS for Health headquarter, using survey approach to 100 employees, and interviews with managers and employees.   Analysis method of structural modelling was operated using SEM PLS 3.0 software to find relationship between research variables. The research has identified some common problems faced by the office in terms of unoptimal work involvement, less cohesive teamwork, career development program does not work, and less conducive organizational environment. This research result shows that teamwork, career development and self development significantly influences work involvement. The career development process also will motivate work involvement.  The results of the study give implication to the organization to focusing on teamwork, career development and self development to influences work involvement.    BPJS for Health office can enhance career development through the dissemination and information disclosure of career systems.  To increase the work involvement, the employees need to develop motivation themselves by facilitating discussion forums and participation between employees to enhance their self-development activities.JEL Classification: E24; J24; O15